(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of acute calculous cholecystitis in elderly patients at Viet Nam – Sweden General Hospital Uong Bi. Methods: A cross-sectional descriptive study combining retrospective and prospective data was conducted on 85 patients aged ≥60 years diagnosed with acute calculous cholecystitis from June 2022 to June 2025 at Viet Nam – Sweden General Hospital Uong Bi. Results: The mean age was 73.7 ± 6.7 years, with a female-to-male ratio of 1.2:1. All patients had comorbidities, of whom 91.8% had at least two chronic diseases; cardiovascular diseases accounted for 97.6%. Right upper quadrant abdominal pain was present in 94.1% of cases, and 37.6% had systemic inflammatory response syndrome. Murphy’s sign was positive in 27.1%, and right upper quadrant abdominal guarding was observed in 29.4%. Leukocytosis (>10 G/L) was found in 51.6% of patients. Abdominal ultrasonography and computed tomography (CT) exhibit high diagnostic sensitivity and specificity for the detection of cholelithiasis and acute cholecystitis. According to the Tokyo Guidelines 2018 severity grading, grade I and II accounted for 84.7% of cases. Conclusion: Acute calculous cholecystitis in elderly patients commonly occurs in those with multiple comorbidities and often presents with atypical clinical features. Combined clinical and paraclinical assessment is essential for early diagnosis.